Can government R&D expenditure promote innovation? New evidence from 37 OECD countries - Ding, Yemin; Yin, Fengchun; Chin, Lee; Zhou, Kun; Taghizadeh-Hesary, Farhad; Li, Yaning (Technological and Economic Development of Economy, 2025)
This research employs a fixed effect model to empirically estimate panel data from 37 OECD countries spanning 2000 to 2021, revisiting the influence of government R&D expenditure on innovation within the theory of marginal diminishing effect. Results reveal a significant positive effect of government R&D expenditure on national innovation capacity, and this influence remains robust under robustness checks. Then, quantile regression uncovers a nuanced pattern, indicating that as a country’s innovation capacity strengthens, the stimulative effect of government R&D expenditure initially rises and subsequently declines. Additionally, incorporating lags of the independent variable at different periods affirms the time lag effect of government R&D expenditure on national innovation capacity. Deeper scrutiny using two fixed effect models including interaction terms reveals a multifaceted mechanism, where government R&D expenditure fosters innovation by promoting bank credit, yet simultaneously suppresses innovation by hindering non-governmental R&D intensity. Lastly, heterogeneity analysis affirms that government efficiency, democracy, ruling party ideology, political stability, and economic freedom moderate the link between government R&D expenditure and national innovation capacity. These insights offer new references for governments to promote innovation.First published online 23 October 2024